2019
DOI: 10.1016/j.amepre.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Sitting Time and Risk of Cardiovascular Disease and Diabetes: A Systematic Review and Meta-Analysis

Abstract: Daniel P Bailey has no financial disclosures. Rachael B Champion has no financial disclosures. David Hewson has no financial disclosures. Suzan Sayegh has no financial disclosures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 37 publications
(74 reference statements)
3
105
0
2
Order By: Relevance
“…The average play time (of more than 20 h per week) in all player status groups shows the importance of gaming in each respondents' life. After long hours at work, school or university, three to four hours of additional gaming result in high amounts of sedentary behavior, which is known to be a risk factor for non-communicable diseases [25][26][27][28][29]. The observed very weak inverse associations of video game play time and self-reported health status, BMI and sedentary behavior are at least pointing in the same direction.…”
Section: Key Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The average play time (of more than 20 h per week) in all player status groups shows the importance of gaming in each respondents' life. After long hours at work, school or university, three to four hours of additional gaming result in high amounts of sedentary behavior, which is known to be a risk factor for non-communicable diseases [25][26][27][28][29]. The observed very weak inverse associations of video game play time and self-reported health status, BMI and sedentary behavior are at least pointing in the same direction.…”
Section: Key Resultsmentioning
confidence: 90%
“…Prolonged screen time, accompanied by long periods of sedentary behavior are recognized as risk factors for numerous chronic diseases [25][26][27] and all-cause mortality [26][27][28][29]. Since gaming and eSports, by their very nature, require long periods of sedentary screen time, it stands to reason that such players pose a high-risk group in exceptional need of health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Sitting time is a sub-component of sedentary behaviour and a common measure of sedentary behaviour [2]. Sedentary behaviour is associated with a range of adverse health outcomes, including, but not limited to: all-cause, cardiovascular and cancer mortality, type 2 diabetes and depression [3][4][5][6][7][8][9][10]. In particular, the combination of high amounts of sedentary behaviour and low amounts of moderate-to-vigorous physical activity is associated with all-cause and cardiovascular mortality [3,7], As such, the World Health Organization is currently in the process of revising the 2010 global physical activity guidelines to include recommendations related to sedentary behaviour across all age groups [11].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the rationale behind the implementation of sit-stand workstations is mainly driven by the evidence from the recently emerging research field of sedentary behaviour, which has shown that prolonged sitting, accumulated during the whole day, seems to be associated with several health risks in the long-term, including type II diabetes [12,13], cardiovascular disease [14,15] and premature mortality [16]. It has been indicated that breaks in sitting, interrupted with light intensity activity, could be beneficial for cardiovascular health [17].…”
Section: Introductionmentioning
confidence: 99%